Functional characterization of intracellular and secreted forms of a truncated hepatitis C virus E2 glycoprotein. - Flint, M; Dubuisson, J; Maidens, C; Harrop, R; Guile, G; Borrow, P; McKeating, J (2000)
The E2 protein of hepatitis C virus (HCV) is believed to be a virion surface glycoprotein that is a candidate for inclusion in an antiviral vaccine. A truncated soluble version of E2 has recently been shown to interact with CD81, suggesting that this protein may be a component of the receptor for HCV. When expressed in eukaryotic cells, a significant proportion of E2 forms misfolded aggregates. To analyze the specificity of interaction between E2 and CD81, the aggregated and monomeric forms of a truncated E2 glycoprotein (E2(661)) were separated by high-pressure liquid chromatography and analyzed for CD81 binding. Nonaggregated forms of E2 preferentially bound CD81 and a number of conformation-dependent monoclonal antibodies (MAbs). Furthermore, intracellular forms of E2(661) were found to bind CD81 with greater affinity than the extracellular forms. Intracellular and secreted forms of E2(661) were also found to differ in reactivity with MAbs and human sera, consistent with differences in antigenicity. Together, these data indicate that proper folding of E2 is important for its interaction with CD81 and that modifications of glycans can modulate this interaction. Identification of the biologically active forms of E2 will assist in the future design of vaccines to protect against HCV infection.